CD28-driven ex vivo generation of stem-like memory CD8 + T cells bypassing CD3/TCR signaling - Fumie Ihara; Yota Ohashi; Evey Y. F. Zheng; Saori Fukao; Rowena Rodrigo; Babak Noamani; Giselle M. Boukhaled; Ben X. Wang; Dong-Hoon Han; Xinyu Wei; Brian D. Burt; Kayoko Saso; et al. (Proceedings of the National Academy of Sciences, 2026)
Adoptive T cell therapies typically rely on ex vivo CD3/CD28 stimulation, which promotes effector differentiation and limits the persistence of transferred cells. Stem cell–like memory T cells (Tscm), with their capacity for self-renewal and multipotency, represent an ideal therapeutic subset but remain difficult to generate at scale. Here, we present a CD3-independent strategy using artificial antigen-presenting cells expressing a membrane-bound CD28 superagonist (αCD28-aAPCs) to expand CD8 + T cells with Tscm-like features. In naïve CD8 + T cells, αCD28-aAPC stimulation initiates a distinct transcriptional and epigenetic program, marked by high TCF1 expression, metabolic fitness, and resistance to exhaustion—key hallmarks of the Tscm phenotype. Mechanistically, this approach circumvents canonical CD3/TCR signaling and notably avoids induction of IRF4, a key transcription factor that drives BLIMP1 upregulation, TCF1 downregulation, and glycolytic commitment during effector differentiation. Instead, sustained CD28 signaling alone reprograms T cells toward a Tscm-like state. Upon subsequent antigen encounter and CD3 engagement, these αCD28-aAPC-expanded T cells mount robust effector responses while retaining superior persistence and antitumor activity in preclinical models. Our findings reveal an underappreciated role of CD28 signaling in guiding Tscm-like fate through IRF4 suppression and establish a platform for generating durable and functionally potent T cell therapies.